Differences in cooperation between social dilemmas of gain and loss - Qingzhou Sun (Society for Judgment and Decision Making, 2021)
In social interactions, people frequently encounter gain (i.e., all outcomes are gains from the status-quo) or loss (all outcomes are losses from the status-quo) social dilemmas, where their personal interests conflict with social interests. We ask whether there are any behavioral differences in social interactions when it comes to gains and losses. Using the Prisoner’s Dilemma games, in three studies we observed that participants were less cooperative in the loss domain than in the gain domain. This effect was robust, not moderated by payoff amount (Study 1), cooperation index (Study 1), domain comparison (Studies 1 and 2), and personal loss aversion (Study 3). Social motive and belief explained this effect: compared to the gain domain, participants in the loss domain aroused more pro-self motive and less prosocial motive, and showed stronger beliefs that their partner would defect, which led them to cooperate less. These findings suggest that gain and loss domains affect individual motivation and belief, subsequently affecting strategic choices in social dilemmas.